Do expectations of fossil fuel owners matter? - Lazou, Rutger (Journal of global ethics, 2024)
To avoid the disastrous effects of climate change, a rapid and drastic transition toward a low-carbon society and economy is required. This transition imposes significant transitional losses on some agents given the benefits they can no longer realize. In economic terms, it leads to the stranding of their assets. This article investigates whether fossil fuel owners could refer to their expectations about the benefits of producing their reserves to justify transitional measures such as exemptions from new rules or financial compensations. It criticizes forward-looking views on the normative relevance of expectations and defends a backward-looking view, which justifies limited claims. It contends that states that are responsible for creating false expectations about regulatory stability should provide compensations to fossil fuel companies for the costs of relying on those expectations. States can be held responsible if they caused this expectation-related harm in a foreseeable and avoidable way, which is only the case if the expectation is reasonable and if they were not put under pressure by the lobbying activities of the fossil fuel industry.